2023
DOI: 10.1088/2053-1591/acece3
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-free synthesis of Ag@TiO2 and CuO@TiO2 photocatalyst: a comparative study of their photocatalytic activity for reduction of nitroaromatics in water

Abstract: The reduction of harmful nitroaromatics to useful amino-aromatics have significant opportunities in synthetic chemistry. Here a visible-light-driven eco-friendly method for the selective reduction of aromatic nitro compounds to their corresponding amines in aqueous solution by using Ag@TiO2 and CuO@TiO2 is described. It was observed that both Ag@TiO2 and CuO@TiO2 are photo-catalytically more efficient compared to bare TiO2 and CuO@TiO2 has higher activity over Ag@TiO2 for the said conversion. The structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…As referred previously by [ 73 ], UV–Vis spectroscopy could easily give insinuation about the signal architecture of any binary or hybrid nanomaterials, wherein, the presence of single SPR peak at an intermediate location between the SPR of the two metals indicates a randomly organized hybrid metal/metal oxides. In this sense [ 36 ], found that the phyto- synthesized CuO-TiO 2 -NCs displayed their characteristic absorption band at 301 nm; however [ 74 ] and [ 75 ], detected an absorption peak of chemically synthesized CuO‐TiO 2 -NCs at 380 and 363 nm, respectively,. Such variations in results could be attributed to the differences in particle surface properties (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As referred previously by [ 73 ], UV–Vis spectroscopy could easily give insinuation about the signal architecture of any binary or hybrid nanomaterials, wherein, the presence of single SPR peak at an intermediate location between the SPR of the two metals indicates a randomly organized hybrid metal/metal oxides. In this sense [ 36 ], found that the phyto- synthesized CuO-TiO 2 -NCs displayed their characteristic absorption band at 301 nm; however [ 74 ] and [ 75 ], detected an absorption peak of chemically synthesized CuO‐TiO 2 -NCs at 380 and 363 nm, respectively,. Such variations in results could be attributed to the differences in particle surface properties (e.g.…”
Section: Resultsmentioning
confidence: 99%